SAR Image Compression Using an Adaptive Algorithm in the Wavelet Domain - Yixin Chen; Salari, E.; Jianming Wei (2006 IEEE International Conference on Electro/Information Technology, 2006)
In this paper, a novel SAR image compression scheme based on adaptive vector quantization and speckle noise suppression in the wavelet domain is presented. The proposed method consists of an edge-preserving speckle noise suppression algorithm followed by an enhanced adaptive vector quantization using Gold-Washing (GW-AVQ) dynamic codebook-refining mechanism to encode the image data. Weighted vector composition and zero vector indexes are applied to further reduce the bitrate. The simulation results show that the proposed algorithm has excellent compression efficiency, and the balance among noise reduction level, distortion level, and compression ratio can be finely adjusted to meet the requirements of various applications